Analisis Tantangan Implementasi Istishna Pada UMKM Pre-Order: Studi Kasus UMKM Konveksi Rifta.Latif - Ahmad Affandi; Najha Khoirotunnisa; Ning Tyas Arlita; Tanadda Shidqi; Mukhlishotul Jannah; Yunita Ria Anjani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the challenges and implementation of the Istishna contract in micro enterprises that apply a pre-order system, using the UMKM Rifta Latif clothing convection as a case study. The pre-order practice generally aligns with the characteristics of Istishna, where goods are ordered and produced based on specific requirements. However, several issues were identified, including unclear contracts, design changes, delays in raw materials, and accounting records that do not fully comply with PSAK Syariah 104. This research employs a descriptive qualitative approach through interviews, observations, and documentation reviews to assess the enterprise’s compliance with PSAK 104. The findings show that although the pre-order system reflects the basic principles of Istishna, revenue recognition, work-in-process recording, and transaction disclosure are not yet fully aligned with the standard. This study contributes to Islamic accounting literature and provides practical recommendations for improving UMKM compliance and transparency.